Encapsulation of luteolin using oxidized lotus root starch nanoparticles prepared by anti-solvent precipitation. (1st December 2021) - Chen, Ying-Ying; Liu, Kang; Zha, Xue-Qiang; Li, Qiang-Ming; Pan, Li-Hua; Luo, Jian-Ping
Abstract: In this study, luteolin-oxidized lotus root starch (OLRS) nanoparticles (NPs) were developed to improve the stability and antioxidant activity of luteolin. Results showed that a stable luteolin-OLRS NPs was formed using luteolin and OLRS (oxidation degree, 15%) in the weight ratio of 3:1, as well as anti-solvent and solvent in the volume ratio of 10:1. Under this condition, the particle size, polydispersity index and zeta-potential of luteolin-OLRS NPs was 305 nm, 0.173 and −20.8 mV, respectively. The analysis of transmission electron microscopy, X-ray diffractometer and Fourier transform infrared spectroscopy demonstrated that the luteolin was successfully encapsulated in OLRS NPs, giving an encapsulation efficiency of 87.2%. The release characteristic and antioxidant activity of encapsulated luteolin were further investigated. Results exhibited that the OLRS NPs enabled luteolin to be stable in simulated gastric fluid and sustained release in simulated intestinal fluid, leading to the enhancement of antioxidant activity of luteolin. Highlights: OLRS NPs represent the oxidized lotus root starch nanoparticles. LRS with oxidation degree of 15% benefits the encapsulation of luteolin. The stability of luteolin was enhanced by OLRS NP encapsulation. The antioxidant activity of luteolin was increased by OLRS NP encapsulation.